POTENSI MODIFIKASI MODEL PIERS UNTUK PREDIKSI LUARAN IBU DENGAN PREEKLAMSIA PADA RUMAH SAKIT TIPE B DI INDONESIA: PENELITIAN RETROSPEKTIF DI RSUD ANSARI SALEH BANJARMASIN, KALIMANTAN SELATAN - Sufriyana, Herdiantri; Handayani, Lisda; Yuliana, Fitri; Syafi'i, Taufiq (UNUSA Press, 2017)
ABSTRACTBackground: Preeclampsia is the most common cause (32%) of maternal deaths in Indonesia. Model Piers(Pre-eclampsia Integrated Estimate Risk) can predict the outcomes / complications of pre-eclampsia andassociated with a reduction in maternal morbidity. This study aims to assess the potential modification of themodel to predict the outcome Piers mothers with preeclampsia in Type B hospitals in Indonesia. Methods:This research is a prognostic with the analytical method and quantitative approach retrospectively. This studyused the capture technique stratified random sampling to obtain the medical records of 160 people withpreeclampsia and 160 controls in hospitals Banjarmasin Ansari Saleh 2014. Identified availability ofvariables in the model along with the outer piers preeclampsia. Performed univariate, bivariate andmultivariate corresponding availability of variables the model Piers. Result: eight of the 48 variables in themodel Piers consistently found in all samples, while output available were complication preeclampsiaeclampsia and/or HELLP syndrome. The gestational age was significantly influent eclampsia for the subjectin this study (P <0.05), HELLP syndrome (P <0.05), and a combination of both (P <0.01). Predictive value ofa logistic regression model with the variables that the outer form of the syndrome HELLP or in combinationwith eclampsia is 0.811 (AUC ROC; CI 95% from 0.636 to 0.986) and 0.767 (AUC ROC; CI 95% 0.666 to0.868), while the prediction of eclampsia was not significant (P> 0.05). Conclusion: Modifications Piersmodels to predict potential outcomes of women with preeclampsia in RS type B in Indonesia if it is supportedby policies and standards that consider this model and supported a larger number of samples.